Analisis Customer Equity Terhadap Pengaruh Digital Marketing - Aghnia Fadilah, Ratu; Hurriyati, Ratih; Dewi Dirgantari, Puspo (Fakultas Ekonomi Universitas Gresik, 2023)
Digital marketing, a social media application, is becoming increasingly popular as a business and communication tool. Analyzing Dunkin' Donuts, this case study attempts to understand customer equity as a method for linking marketing programs and the level of likelihood of providing future profits for the company. With the size of the Dunkin Donuts company, this case study explores how customer equity, especially if the implementation of a digital marketing system, which is currently busy being the main source of Indonesian people who become Dunkin Donuts customers, has used digital access such as social media. Because this case study explores Dunkin Donut's digital marketing system and the influence of customer equity, especially in Indonesia.